Forensic Stylistic Analysis on Suicide Note of A Family of the Elementary School Teacher in Malang - Manalu, Lidya Arella Chaterina; Fila Alfia; Parinduri, Afrahul Fadhillah; Rangkuti, Rahmadsyah (Talenta Publisher, 2024)
This research delves into the realm of forensic stylistic analysis by examining a poignant suicide note penned by a family of elementary school teachers in Malang. Through a meticulous exploration of the emotional intricacies and linguistic characteristics of the note, the study seeks to unravel the underlying motives and sentiments of the authors. Employing techniques such as semantic and sentiment analysis, the research aims to uncover the deeper meanings and emotional nuances embedded within the message. The study sheds light on the enduring presence of love and familial bonds even amidst challenging circumstances, showcasing expressions of care and emotional connections within the notes. The findings underscore the importance of recognizing signs of emotional distress and providing appropriate support for individuals in need. This research contributes to a better understanding of suicide notes within the realm of forensic stylistics and emphasizes the significance of empathy and intervention in times of emotional crisis.